1997
DOI: 10.1051/lait:1997110
|View full text |Cite
|
Sign up to set email alerts
|

Influence of raw milk microflora on the characteristics of Swiss-type cheeses : II. Biochemical and sensory characteristics

Abstract: Summary -Using the same microfiltered milk, three 'raw milk' Swiss-type minicheeses were made after addition of three different retentates; one, remaining bacteria-free, was used as reference. The experiment was repeated three times at two different seasons. Factorial discriminant analyses were made on biochemical, physico-chemical and microbiological data at 12 weeks (end of warm storage, 18 "C) and 24 weeks (end of cold storage, 7 "C), At each ripening period, 'raw milk' cheeses were easily and significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 24 publications
4
45
0
4
Order By: Relevance
“…A part of the differences in micro-organisms diversity in milk from different farms or plants [37,39,44,84] could be due to animal feeding. It has been recently suggested that terpenes, whose plant-specific origin has been documented, may have an indirect impact on cheese sensory properties by modifying the dynamics of the microbial ecosystem during cheese-making and ripening.…”
Section: Microbial Ecosystemmentioning
confidence: 99%
“…A part of the differences in micro-organisms diversity in milk from different farms or plants [37,39,44,84] could be due to animal feeding. It has been recently suggested that terpenes, whose plant-specific origin has been documented, may have an indirect impact on cheese sensory properties by modifying the dynamics of the microbial ecosystem during cheese-making and ripening.…”
Section: Microbial Ecosystemmentioning
confidence: 99%
“…Comparison of cheeses made from raw milk with those made from microfiltered or pasteurised milk has shown that the raw milk flora plays an essential role in the development of the sensory characteristics of hard cheeses. In most cases it was found that elimination of the raw milk flora leads to a less intense cheese flavour [6,10,17]. Several studies further indicated that mesophilic adjuncts can exert a positive effect on flavour [5,8,19].…”
Section: Introductionmentioning
confidence: 99%
“…The above-mentioned authors observed differences in volatile compound composition in cheeses -whether these compounds were of microbial origin or originated from the feed -that may be linked to differences in flavour. On the one hand, there may be a specific type of microflora in each production zone, as has been demonstrated [18,21], which would lead to significant variations in the sensory quality of the cheese [7,12,20]. On the other hand, certain compounds present in forage, such as terpenes, may be found later in the dairy products [40] and thereby contribute to cheese aroma [8,9,22,24,39].…”
Section: Introductionmentioning
confidence: 99%